Influence Of Potassium Citrate Or Ascorbic Acid On The In-Vitro Antibacterial Activity Of Some Antibiotics - Odelola, H. A.; Oloyede, A..Y. (The Nigerian Journal of Pharmacy, 1992)
Bacteriostatic activity of each of four antibiotics was determined singly and in combination with either potassium citrate or ascorbic acid employing three bacterial genera as test organisms. Results obtained in the study showed that presence of ascorbic acid with gentamicin or tetracycline potentiatecl bacteriostatic activity of each of these antibiotics against Pseudomonas aeruginosa and Escherichia coli espectively. While combination of potassium citrate tremendously enhanced in-vitro activity of ampicillin, tetracycline and cefuroxime against Pseudcmonas aeruginosa, Staphylococcus aureus and Escherichia coli. It was also observed that potassium itrate improved the sensitivity of some strains of Pseudomonas aeruginosa hitherto resistant to ampicillin. (Preview the download for more on the abstract.)